2010
DOI: 10.1055/s-0030-1258083
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Heck-Type Coupling of Allyl Esters: β-Hydride versus β-Acetoxy Elimination

Abstract: This account presents recent progress in palladiumcatalyzed Heck-type reactions of allyl esters with aryl halides, arylmetallic reagents, or arenes. Many improvements have been achieved to control the regioselectivity of b-hydride or b-acetoxy elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Allylic esters are commonly used as allylation reagents in organic synthesis. Jiao et al, White et al, and Xiao et al reported oxidative Heck reactions of allylic esters with arylboronic acids, which occurred via β-hydride elimination rather than β-OAc elimination. In 2011, Liu et al reported olefination of (poly)­fluoroarenes with allyl esters via an oxidative coupling process using [Pd­(OAc) 2 ] as the catalyst and AgOAc as the base and the oxidant.…”
Section: C-c Bond Forming Reactionsmentioning
confidence: 99%
“…Allylic esters are commonly used as allylation reagents in organic synthesis. Jiao et al, White et al, and Xiao et al reported oxidative Heck reactions of allylic esters with arylboronic acids, which occurred via β-hydride elimination rather than β-OAc elimination. In 2011, Liu et al reported olefination of (poly)­fluoroarenes with allyl esters via an oxidative coupling process using [Pd­(OAc) 2 ] as the catalyst and AgOAc as the base and the oxidant.…”
Section: C-c Bond Forming Reactionsmentioning
confidence: 99%